PENGARUH BUNGKIL INTI SAWIT FERMENTASI DALAM PAKAN TERHADAP PERTUMBUHAN IKAN MAS ( Cyprinus carpio L.) - M. Amri (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2007)
The study effect of Fermented Palm Kernel Cage (FPKC) in feed on growth of Cyprinus carpio L. was done to evaluate the utilization of palm kernel cage increasing the quality by fermentation technology as a feed in ration to Cyprinus carpio L. performance and get a good level in ration. This experiment was set in a Randomized Completely Design with four treatments and four replicates. Treatments were diets with : A (12% PKC), B (15% FPKC), C (18% FPKC), and D (21% FPKC). Results of experiment indicated that the feed consumption body weight gain, feed conversion and income over feed cost was in proved by 18% FPKC in the diet.